Advances in Molecular Simulation - Borówko, Małgorzata (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Molecular simulations are commonly used in physics, chemistry, biology, material science, engineering, and even medicine. This book provides a wide range of molecular simulation methods and their applications in various fields. It reflects the power of molecular simulation as an effective research tool. We hope that the presented results can provide an impetus for further fruitful studies.